Le nozioni di emissione deliberata, immissione in commercio e coltivazione di ogm: commento critico alla direttiva 2001/18/CE alla luce della direttiva 2015/412/UE (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The concepts of deliberate release, placing on the market and OGM cultivation: A critical comment to directive 2001/18/CE in the perspective of directive 2015/412/UEAbstract: The article aims to evaluate the directive 2001/18 concerning the deliberate release into the environment of genetically modified organisms (GMOs). The analysis reveals not only the internal inconsistency of the directive, but also identifies the problems which characterize, firstly, the legal definition of «deliberate release» of GMOs, secondly the notion of «placing on the market» of GMOs and thirdly the relation between the EU authorization to place GMOs on the market and the Member State authority to ban the cultivation of GMO crops.
Keywords: EU Directive 2001/18; deliberate release of GMOs; placing on the market of GMOs; cultivation of GMO crops; cultivation ban on GMOs